2015
DOI: 10.1016/j.jped.2015.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics for the treatment of upper and lower respiratory-tract infections in children: systematic review based on randomized clinical trials

Abstract: Despite the encouraging results - reducing new episodes of respiratory infections - the authors emphasize the need for further research, especially in developing countries, where rates of respiratory infections in children are higher when compared to the high per capita-income countries identified in this review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 42 publications
0
22
0
2
Order By: Relevance
“…However, other trials have shown that the use of probiotics can decrease the occurrence of infection in traumatic, surgical, and pediatric patients. [30][31][32] Most of the patients in this trial were surgical cases. Only 9 patients required mechanical ventilation for >3 weeks, which is a major risk factor for VAP.…”
Section: Discussionmentioning
confidence: 99%
“…However, other trials have shown that the use of probiotics can decrease the occurrence of infection in traumatic, surgical, and pediatric patients. [30][31][32] Most of the patients in this trial were surgical cases. Only 9 patients required mechanical ventilation for >3 weeks, which is a major risk factor for VAP.…”
Section: Discussionmentioning
confidence: 99%
“…A Cochrane review concludes that saline irrigations are not likely to be effective in adults 20. We did not find trials studying the effect on common cold symptoms for the following treatments: probiotics,272829 garlic,18 Chinese medicinal herbs,30 vapour rub,22 eucalyptus oil, honey,31 ginseng,23 and increased fluid intake 33…”
Section: What Is the Evidence Of Uncertainty?mentioning
confidence: 95%
“…Yeasts as probiotic improve nutrient absorption/assimilation from food and digestion. LAB used as probiotic stimulates and balances the immune system [2], prevents vaginal and urinary tract infections [10,11], prevents and treats side effects of antibiotic therapy [12], aids in digestion of lactose and dairy products by reducing lactose intolerance [13,14] helps in the regulation of bowel movements [15], reduces the toxic load of liver [16,17] inhibits the growth of bacteria which produces nitrates in bowel as production of nitrates could in certain cases cause cancer [2], prevents excessive growth of pathogenic microbes such as candida, E. coli, Helicobacter pylori and Salmonella [18][19][20][21][22] reduces the incidence of yeast infections [11], virginities and candidacies [23], calms down the colon irritation following surgery, supports healthy skin in youth, and is the primary bacteria in infants, which helps them to grow and develop their immune system [24,25], therapeutic for upper respiratory complaints [26], act as remedy for bad breath (halitosis) [27], increase ability to synthesize vitamin B, manufactures vitamin B complex [28], increase the ability to absorb calcium [29,30] reduce the occurrence of bladder cancer [31], prevent and manage atopic dermatitis (eczema) in children [32]. Evidences revealed that all the health claims linked to probiotics are mainly strain specific and the health claim raised by one strain could not be assumed for another strain, even though both comes under the same species [33].…”
Section: Health Claims For Probioticsmentioning
confidence: 99%
“…The reduced intestinal transit time of yogurt is the alternate reason for the reduction of lactose intolerance thereby allowing slow lactose assimilation. The lactase producing bacteria present in yogurt is Lactobacillus acidophilus, which aids in the digestion and lactose absorption [26,40]. Other lactase producing bacteria preventing lactose intolerance are Lactobacillus bulgaricus and Streptococcus thermophiles [41].…”
Section: Lactose Intolerancementioning
confidence: 99%